(3GdGYdGfs - (3GMeO eMeO(B, (3GdeUQjs ((3GdGScfOQjI(B:s (3eDSSI THGH GdLGeYjI(B,s, 1992)
(3eaghe h GgejI GdGYdGf , OhQ GdGYdGf aj JfejI GdGfTWIGdJLGQjI hGdNOejI, GdOYhi GdGYdGfjI, JNWjW h GNQGL GdGYdGf, hSGFd GdGYdGf ,hcGdGJ GdGYdGfs
(3HjHdjhZQGajG (B: (3U(B.109-110s
Keywords: (3GdGYdGfs; (3GdMedGJ GdGYdGfjIs; (3GdOYGjIs; (3GdedUbGJs